Peran Pembelajaran PAI dalam Meningkatkan Kualitas Wawasan Agama Islam pada Era Digital di SMP SWASTA MUHAMMADIYAH 8 MEDAN - Hasri Rahwaniko; Nurjannah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This research expresses an opinion about the role of learning in Islamic religious education. students in class XI at SMP Muhammadiyah 8 Medan. This research presents problems in learning Islamic religious education in the digital era/industrial revolution era 4.0. This era, directly or indirectly, has ushered in many changes in the life of Islamic religious education. Islamic religious education is now faced with challenges. new problems, demands and needs that have never existed before. So it is necessary to update and innovate systems, governance, curriculum, human resource competencies, facilities and infrastructure, culture, work ethic, and so on. The role of Islamic Religious Education teachers in maintaining students' religious values and the condition of students' religiosity at Muhammadiyah Private Middle School 8 Medan in maintaining Islamic values among students in the digital era. This type of research is descriptive qualitative, namely explaining in depth what it is. According to the data collected. The informant in this research was 1 Islamic Religious Education teacher. Data collection techniques are observation, interviews.